A Time for Recommitment: Building the New Relationship between Jews and Christians - Christians; Jews, International Council of (Studies in Christian-Jewish Relations, 2011)
At the 2009 Berlin ICCJ conference, the International Council for Christians and Jews issued a call to recommitment to Christian and Jewish communities around the world.